Smartcuts : how hackers, innovators, and icons accelerate success - Snow, Shane (Harper Business, 2014)
Delving into the reasons why some people and some organizations are able to achieve incredible things in implausibly short time frames, this thoughtful book shows how each of us can use "smartcuts" to rethink convention and accelerate success. --